IMPLEMENTING A SUSTAINABLE PURCHASING POLICY: AN EXPLORATORY STUDY IN THE COLAS GROUP - Allal-Chérif, Oihab (European Scientific Journal, ESJ, 2015)
This article addresses the contribution of the purchasing function to Corporate Social Responsibility (CSR). Indeed, the purchasing function is playing an increasingly important role in businesses, averaging over 60% of turnover. Simultaneously, managers integrate societal and environmental challenges in the management of internal and external relations. Sustainable purchasing policies, aimed at changing practices throughout the value chain, are deployed. Suppliers are therefore gradually mobilized to implement more responsible practices, and invited to commit themselves through sustainability charters and certification. That leads to the research question: how to implement a sustainable purchasing policy aligned with the corporate strategy? The CSR approach represents a particularly difficult challenge for some companies, as in the construction and civil engineering sector. The Colas Group, world leader in road construction, faces this difficulty that implies radical changes in its relations with its suppliers. Faced with the image of environmental pollution, landscape destruction, illegal labor, and endangerment of its workers, the Colas Group has implemented a progressive, rigorous and structured sustainable approach. Through participatory action research during a one year immersion, a case study of the Colas Group has been developed to analyze this approach and determine its benefits and limits. The particularly difficult context of the implementation of this sustainable purchasing policy – in a multinational, in a post-merger period, in an unfavorable sector and during an economic crisis – implies potential transferability of some practices studied in this specific case.